Religious Tolerance Education in The Book Log In: Habib and Onad by Husein Ja’far Al-Hadar - Latifatul Muasyaroh; Luluk Ifadah; Ana Sofiyatul Azizah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe the concept of religious tolerance education in the book Log In: Habib and Onad by Habib Husein Ja’far Al-Hadar and its relevance to Islamic Religious Education. This study employs a narrative approach and utilizes library research using a descriptive qualitative method. The primary data source is the book Log In: Habib and Onad, while secondary data sources include relevant books, journals, and previous studies. Data collection techniques include observation and note-taking, documentation, and literature review. Data analysis employs content analysis. The results of the study indicate that the concept of religious tolerance education in the book consists of five main concepts, namely recognizing the rights of others, respecting the beliefs of others, mutual understanding and empathy, awareness and honesty, and agreeing to differences. These five concepts are relevant to Islamic Religious Education (IRE) learning in terms of objectives, content, methods, and evaluation to foster moderate, humanistic attitudes, and respect for diversity. Keywords: Religious Moderation, Tolerance Education, PAI Learning.